Groundwater spatial dynamics and endogenous well location - Katic, Pamela G. (Springer, 2015)
Groundwater economic models have refined optimal extraction rules while lagging behind in the study of optimal spatial policies. This paper develops a theoretical model to estimate welfare gains from optimal groundwater management when the choice variable set is expanded to include well location decisions as well as optimal groundwater extraction paths. Our theoretical results show that if there is spatial heterogeneity in groundwater, the welfare gains from optimal location of wells are substantial even if extraction rates are unregulated. Furthermore, second-best economically defined spacing regulations may possibly have better efficiency results (and lower implementation costs) than first-best uniform taxes or quotas. An application of the model to a real-world aquifer shows the importance of including well location decisions in spatially differentiated groundwater models and the need for (1) robust estimates of the gains from optimal management and; (2) spatially explicit regulations.